STS and Innovation: Borderlands, Regenerations and Critical Engagements - Alan Irwin (Engaging Science, Technology, and Society, 2023)
This introduction to a thematic collection on the relationship between STS and innovation poses three main questions. When it comes to engaging with and acting upon socio-technical change, is ‘innovation’ part of the solution or of the problem? How should we view the relationship between STS approaches to innovation and neighbouring fields, especially Innovation Studies (IS)? What new conceptual and empirical resources can STS bring to the study of innovation (including the possible redefinition and reframing of the term itself)?